Current Evidence of Combination of Oral Antibiotics and Mechanical Bowel Preparation in Elective Colorectal Surgery and Their Impact on Anastomotic Leak. (February 2020) - Ioannidis, Argyrios; Zoikas, Athanasios; Wexner, Steven D.
Anastomotic leak represents a potentially catastrophic complication following colorectal surgery. Preoperatively, bowel preparation has a significant role in anastomotic leak prevention, but the optimal method remains unclear. Recently, numerous studies have supported combined mechanical bowel preparation and oral antibiotics prior to elective colorectal operations. Based on the plethora of recent data, we hope that surgeons will routinely use a combination of oral antibiotics and mechanical bowel preparation prior to elective colorectal resections.